2013
DOI: 10.1007/s11033-013-2749-2
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cell cycle regulatory factors hus1, gadd45a, rb1, cdkn2a and mre11a correlates with expression of clock gene per2 in human colorectal carcinoma tissue

Abstract: Deregulated expression of clock gene per2 has previously been associated with progression of cancer. The aim of the present study was to identify genes related to per2 expression and involved in cell cycle control. Patients surgically treated for colorectal carcinoma with up-regulated and down-regulated per2 expression in cancer versus adjacent tissue were studied. Total RNA from cancer tissue of these patients was used to specify genes associated with altered per2 expression using the Human Cell Cycle RT(2) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 84 publications
0
14
0
Order By: Relevance
“…Recent studies have considered that clock gene PER2 can regulate cell cycle genes, sequentially, producing a close relationship with the occurrence of cancers (14,(27)(28)(29). In the present study, however, we considered questions on two other aspects.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recent studies have considered that clock gene PER2 can regulate cell cycle genes, sequentially, producing a close relationship with the occurrence of cancers (14,(27)(28)(29). In the present study, however, we considered questions on two other aspects.…”
Section: Discussionmentioning
confidence: 97%
“…PER2 is reduced in various types of cancer cells, including breast cancer, neck squamous cell carcinoma, prostate cancer, colorectal cancer, hepatocellular carcinoma, skin cancer, gastric cancer, and myeloid leukemia (1,10,14,(20)(21)(22)(23)(24)(25)(26). PER2 can regulate downstream plentiful cell cycle genes, such as CyclinA, CyclinB1, CyclinD1, CyclinE, p53, and C-myc (14,(27)(28)(29). Our previous study also demonstrated that PER2 expression is decreased in oral squamous cell carcinoma (OSCC) (13), and lower expression of PER2 in OSCC cells increased the expression of downstream cell cycle genes, such as CyclinA2, CyclinB1, CyclinD1, CDK4, CDK6, and E2F1, and decreased expression of p53, p16, and p21 (30).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Cdc20-resistant conductin suppressed Wnt signaling and subsequently attenuated colony formation of colorectal cancer cells (Hadjihannas et al, 2012). Interestingly, in a separate study, it has also been observed that expression of Cdc20 was decreased in the human colorectal cancer tissues compared with the proximal tissues (Storcelova et al, 2013), suggesting that further in-depth investigation is needed to define the exact role of Cdc20 in colorectal cancer.…”
Section: Role Of Cdc20 In Human Malignanciesmentioning
confidence: 99%
“…Multiple intracellular signaling proteins involved in stress-responsive cascades, e.g . ATM, p53, MRE11, BRCA1 and CDKN2A, play important roles in both cell cycle/DDR control as well as circadian clock regulation [24, 26, 28-30]. Recently we have also demonstrated that G protein-coupled receptor (GPCR)-related signaling proteins, linked to premature aging, can also effectively connect energy metabolism, oxidative stress responses and DDR activity [31-34].…”
Section: Introductionmentioning
confidence: 99%